Conjugative transfer of chromosomally encoded antibiotic resistance from Helicobacter pylori to Campylobacter jejuni - Oyarzabal, Omar A.; Rad, Roland; Backert, Steffen (Journal of Clinical Microbiology, 2007)
Many strains of Helicobacter pylori are naturally competent for transformation and able to transfer chromosomal DNA among different isolates using a conjugation-like mechanism. In this study, we sought to determine whether H. pylori can transfer DNA into Campylobacter jejuni, a closely related species of the Campylobacterales group. To monitor the transfer, a chromosomally encoded streptomycin resistance cassette prearranged by a specific mutation in the rpsL gene of H. pylori was used. Mating of the bacteria on plates or in liquid broth medium produced C. jejuni progeny containing the streptomycin marker. DNA transfer was unidirectional, from H. pylori to C. jejuni, and the progeny were genetically identical to C. jejuni recipient strains. DNase I treatment reduced but did not eliminate transfer, and DNase I-treated cell supernatants did not transform, ruling out phage transduction. Recombinants also did not occur when the mating bacteria were separated by a membrane, suggesting that DNA transfer requires cell-to-cell contact. Transfer of the streptomycin marker was independent of the H. pylori comB transformation system, the cag pathogenicity island, and another type IV secretion system called tfs3. These findings indicated that a DNase I-resistant, conjugation-like mechanism may contribute to horizontal DNA transfer between different members of the Campylobacteriales group. The significance of this DNA uptake by C. jejuni in the context of acquiring antibiotic resistance is discussed. Copyright © 2007, American Society for Microbiology. All Rights Reserved.
Created from Fastlane, Scopus look-up